Quin Franciscan Friary, west door jamb, arch and hood - O'Donovan, Danielle (My University, 2008)
West door jamb, arch and hood moulding. From intrados, moulding comprises: quadrant, hollow chamfer, right-angled rebate, hollow chamfer, quadrant. The hood comprises: hollow, free-standing fillet, hollow, chamfer. This door, with its pointed arch contained within a square moulded label, is very similar in design to that at Bishopsquarter. The moulding is identical.
west door
Keywords: quadrant; Architecture, Gothic -- Ireland; Quin Abbey; Architecture, Franciscan; Gothic doorways; Late Medieval; roll moldings; moldings, hollow; hood moldings